Hepatics in surroundings of the town of Lazarevskoe (Western Caucasus, Russia) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The annotated list of hepatics in surroundings of Lazarevskoe contains 42 taxa on specific / infra-specific level. 200 specimens were collected and identified by the authors. Frullania fragilifolia, Porella arboris-vitae var. killariensis, Radula complanata var. alpestris are new to Caucasus. Calypogeia arguta and Pellia epiphylla are new to the Russian part of Caucasus. Six species are reported for the first time from the Sochi National Park. Two species of the European Red Data Book and five species included in the Red Data Book of the Krasnodar Territory were recorded.
Keywords: Hepatics, flora, rare species, Caucasus, Lazarevskoe, Sochi National Park, Red Data Book of European Bryophytes.